Influences of micro-blasting as surface treatment technique on properties and performance of AlTiN coated tools. (October 2017) - Jacob, A.; Gangopadhyay, S.; Satapathy, A.; Mantry, S.; Jha, B.B.
Graphical abstract: Highlights: Micro-blasting as both pre- and post-treatment for AlTiN coating. Influence of micro-blasting on microstructure, grain size, chemical composition studied for the first time. Effect of both treatments on dry machining performance of AlTiN coated tool investigated for the first time. Both prior and post treatment found to remarkably enhance coating characteristics and cutting performance. Abstract: It is essential to sustain ever increasing challenges faced by cutting tool manufacturers in improving the performance of the tools during machining of difficult-to-cut materials which have been developed in recent times. Although coated tools have found wide application in industries, there still remains a considerable scope of improvement of the properties of coatings with a view to achieve environment-friendly dry machining. Surface treatment has been identified as one of the possible avenues which has the potential to augment properties and performance of coated tools in dry machining. The current research work has utilized micro-blasting of cutting tool substrates prior to deposition and coating after deposition in order to recommend optimal surface treatment technique for the development of a coated tool. AlTiN coating is deposited using cathodic arc evaporation and effect of micro-blasting both as pre-treatment as well as post treatment methodology is investigated on micro-structure, crystallographic orientation, grain size, coating adhesion and hardness. Effect of surface treatment has been finally studied during machining of 17-4 pH martensitic stainless steel. As-deposited AlTiN coating without any treatment has along being considered for comparison. Results have clearly indicated micro-blasting as pre-treatment technique considerably enhances coating adhesion while post treatment results in increase in hardness. Since both the properties are essential in combating coating delamination and improving wear resistance, AlTiN coating with both pre- as well as post treatment techniques have demonstrated excellent promise in dry machining application.